Case Report: Mild BRIC-like cholestasis despite a gross USP53 deletion—novel findings and literature review - Nuzhnaya, Ekaterina; Cherevatova, Tatiana; Lotnik, Ekaterina; Shagiazdanova, Aleksandra; Markova, Zhanna; Filimonova, Ekaterina; Parshina, Olga; Buianova, Anastasiia; Bobreshova, Anastasia; Marakhonov, Andrey; Semenova, Natalia (Frontiers in Genetics, 2025)
We report a pediatric case of cholestatic liver disease associated with two novel compound heterozygous variants in the USP53 gene: a truncating c.1219A>T (p.Lys407*) variant inherited from the father and a maternally inherited gross deletion involving exons 13–19. Despite the disruptive nature of these variants, the patient presented with a benign recurrent intrahepatic cholestasis (BRIC) characterized by episodic pruritus, jaundice and elevated bile acids with preserved liver function between episodes. Liver histology revealed fibrosis with a cholestatic component, consistent with mild progressive familial intrahepatic cholestasis (PFIC) features. Molecular diagnosis was confirmed by whole-exome sequencing (WES), chromosomal microarray, and Sanger sequencing. A systematic review of 39 published cases was conducted, revealing that USP53-related disease exhibits broad clinical variability, ranging from BRIC to PFIC7. Our findings expand the spectrum of USP53 variants, underscore the relevance of large deletions and emphasize the inclusion of USP53 in genetic panels for idiopathic low-gamma-glutamyl transferase (GGT) cholestasis.